Factores ambientales y su influencia en las infecciones respiratorias agudas en niños menores de 10 años. Parroquia Barreiro Cantón Babahoyo Los Ríos. Septiembre 2017 a febrero 2018 - Meléndez Benítez, Yanina Yaritza (2018)
The purpose of this research is to analyze how environmental factors influence acute respiratory infections in children under 10 years of age; and develop prevention techniques that manage to avoid complications and thus reduce infant mortality rates. For the analysis of this study, a deductive method was required due to the nature of the research, from this a quantitative and qualitative approach was used to know the background and the evolution of ARI in children under 10 years of age to demonstrate the causes that affect this disease. In addition, the analysis of results was carried out through statistical tools that will allow demonstrating that the present work is valid. Within the field research aspects and factors that influence the influence of the IRA were identified, considering that one of the problems that arise is the little knowledge that the inhabitants have about the IRA, they do not have the necessary economic resources and the lack of care or prevention techniques by specialized health, therefore the government should implement new prevention programs and qualified personnel to give talks to people who can control ARI and reduce child mortality rates in the country.